THE PEDAGOGY COURSE IN BRAZIL: HISTORY AND INFLUENCE FOR WORKING PEDAGOGUES - Bruna Pereira Alves Fiorin; Liliana Soares Ferreira (Editora da Universidade de Santa Cruz do Sul, 2013)
The work of pedagogues is influenced by several factors, among them, by formation in Pedagogy Course. Accordingly, we sought to understand how the Pedagogy Course influenced the work of pedagogues participating in the study. Therefore, we applied a questionnaire and conducted dialogue with a group of 15 pedagogues who have completed this course at a university in the state (RS), 2005-2010. The data were analyzed by content analysis based on the categories Work, Pedagogy Course and Pedagogues. The research enabled realize transformations which the Pedagogy Course passed since its inception to the present. Finally, there was the influence of this course in the formation of professional surveyed, discussing its importance to professional training, the pedagogical project, the theory / practice and stage, noting that there are still points to be problematized in relation to the organization of the course and the work that pedagogues develop.